Coffee and energy drink use patterns in college freshmen: associations with adverse health behaviors and risk factors - Dace S. Svikis; Pamela M. Dillon; Steven E. Meredith; Leroy R. Thacker; Kathryn Polak; Alexis C. Edwards; David Pomm; Danielle Dick; Kenneth Kendler; Spit for Science Working Group (BMC, 2022)
Abstract Background Public health concern over college students mixing caffeine-containing energy drinks (EDs) and alcohol has contributed to an array of ED-focused research studies. One review found consistent associations between ED use and heavy/problem drinking as well as other drug use and risky behaviors (Nutr Rev 72:87-97, 2014). The extent to which similar patterns exist for other sources of caffeine is not known. The present study examined associations between coffee and ED consumption and alcohol, tobacco and other drug use; alcohol use problems; and parental substance abuse and mental health problems in a sample of college freshmen. Methods Subjects were N = 1986 freshmen at an urban university who completed an on-line survey about demographics; caffeine; alcohol, tobacco and other drug use; and family history. The sample was 61% female and 53% White. Chi-square analyses and multivariable binary or ordinal logistic regression were used to compare substance use, problem alcohol behavior, and familial risk measures across 3 caffeine use groups: ED (with or without Coffee) (ED + Co; N = 350); Coffee but no ED (Co; N = 761); and neither coffee nor ED (NoCE; N = 875) use. Results After adjusting for gender and race, the 3 caffeine use groups differed on 8 of 9 symptoms for alcohol dependence. In all cases, the ED + Co group was most likely to endorse the symptom, followed by the Co group and finally the NoCE group (all p < .002). A similar pattern was found for: use 6+ times of 5 other classes of drugs (all p < .05); extent of personal and peer smoking (all p < .001); and paternal problems with alcohol, drugs and anxiety/depression as well as maternal alcohol problems and depression/anxiety (p < .04). Conclusions The response pattern was ubiquitous, with ED + Co most likely, Co intermediate, and NoCE least likely to endorse a broad range of substance use, problem alcohol behaviors, and familial risk factors. The finding that the Co group differed from both the ED + Co and NoCE groups on 8 measures and from the NoCE group on one additional measure underscores the importance of looking at coffee in addition to EDs when considering associations between caffeine and other risky behaviors.